2012
DOI: 10.1007/s11914-012-0112-5
|View full text |Cite
|
Sign up to set email alerts
|

Systems Genetics: A Novel Approach to Dissect the Genetic Basis of Osteoporosis

Abstract: From the early 1990s to the middle of the last decade, the search for genes influencing osteoporosis proved difficult with few successes. However, over the last 5 years this has begun to change with the introduction of genome-wide association (GWA) studies. In this short period of time, GWA studies have significantly accelerated the pace of gene discovery, leading to the identification of nearly 100 independent associations for osteoporosis-related traits. However, GWA does not specifically pinpoint causal gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Also, novel transcripts, gene fusion, and alternative splicing may not be detected because of the dependence on commercial chips. To address these issues, transcriptome sequencing (RNA-seq) could be an attractive alternative [71]. …”
Section: Gene Expression Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, novel transcripts, gene fusion, and alternative splicing may not be detected because of the dependence on commercial chips. To address these issues, transcriptome sequencing (RNA-seq) could be an attractive alternative [71]. …”
Section: Gene Expression Studiesmentioning
confidence: 99%
“…Most of the genetic variants or genomic regions that have so far been identified by GWASs of osteoporosis-related traits have been intronic or intergenic [71]. These variants or regions could be transcription factor binding sites that regulate or affect gene expression [71], but precisely how they might influence bone mass awaits further investigation.…”
Section: Implications For Pathogenesismentioning
confidence: 99%
“…Linkage analysis [30][31][32] has been successful in identifying numerous quantitative trait loci involved in BMD regulation, but these findings have not been replicated between linkage studies and most of the genetic variables resulting from linkage signals remain to be identified. However, until now, identification of genes influencing osteoporosis by linkage analysis proved difficult with few successes [33], and positional cloning of genes underlying the associated trait loci appears intricate. Furthermore, meta-analysis of 11,842 subjects from nine linkage studies found no loci were associated with BMD [34].…”
Section: A Linkage Analysismentioning
confidence: 99%
“…GWAS is a powerful tool to investigate the genetic architecture of polygenic disorders arising from nucleotide polymorphisms and have been successful in identifying osteoporosis predisposition genes [29,48,49]. GWASs have recently identified nearly 100 independent associations for osteoporosis susceptibility traits [33]. GWAS has a major advantage over the CGAS by offering the possibility to identify novel susceptibility genes and pathways.…”
Section: Genome Wide Association Studies (Gwas)mentioning
confidence: 99%
“…As an emerging and novel approach, systems genetics has been applied to complex diseases from a systems-level perspective to determine how genetic variations perturb cellular systems and ultimately disease (12). In a systems genetics study, data from genome, transcriptome, epigenome, proteome, metabolome, and interactome will be analyzed using a suite of analytical approaches including GWAS and network analysis (13).…”
mentioning
confidence: 99%